Rancang Bangun Sistem Informasi Rumah Bersalin (Studi Kasus Rumah Bersalin Bidan Ni Wayan Suriati) - Surya, I Putu Agus Hendrayana; Wibowo, Januar; Amelia, Tan (Jurnal JSIKA, 2012)
Midwives at the maternity hospital Ni Wayan Suriati there are some problems that often arise in the process of patient care caused by the manual system is still not running properly so that the information is conveyed to the patient or to the part related to patient care. Another constraint that is making statements that are often slow to the owner of the maternity hospital. Design of the maternity hospital information systems can be used to design and build the system so the system can improve the manual system is not run well in advance and integrate all the parts in the system so that patient services could be improved with a system that works well and reduces recording errors and lack irregularity and the completeness of the recording of complaints that may impact on patient care better organized and easier for patients, midwives and related parts to get the information. After doing the design and manufacture of maternity information system the results obtained when the system is designed and made ​​applicable the patient care process, the purchase can be computerized and integrated drug between each part of the maternity hospital and the information can be conveyed by both the parties that deal in system of maternity homes. Keywords: information systems, maternity homes